2015
DOI: 10.1016/j.pec.2015.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Closing calls to a cancer helpline: Expressions of caller satisfaction

Abstract: A c c e p t e d M a n u s c r i p t  We examine 99 calls to the Macmillan cancer helpline using Conversation Analysis.  We focus on endogenous measures of caller satisfaction expressed during the call.  Callers express differing levels of satisfaction in the closing of the call.  Expressions of dissatisfaction cause difficulties in closing the call.  Patterns of communication may benefit organisations in how to manage calls. A c c e p t e d M a n u s c r i p t 3 AbstractObjective: This study provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…This kind of specificity is commonly lacking in patient burden calls. P responds with "Excellent," (8), Wonderful," (10) and "Oh that's absolutely fine," (12), indicating that this offer is more than satisfactory (see also [14] for endogenous cues to patient satisfaction).…”
Section: Examples Of Successful Practice and Reduced Patient Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of specificity is commonly lacking in patient burden calls. P responds with "Excellent," (8), Wonderful," (10) and "Oh that's absolutely fine," (12), indicating that this offer is more than satisfactory (see also [14] for endogenous cues to patient satisfaction).…”
Section: Examples Of Successful Practice and Reduced Patient Burdenmentioning
confidence: 99%
“…They found that receptionists who maintain a narrow focus on the task at hand, while ignoring patient comments and apologies, were less effective in meeting the patients' needs than receptionists with more patient-centred orientations. Hewitt et al's [7,11,12] work is, to the best of our knowledge, the only study of patient care that also analyses real-time interaction, but in faceto-face encounters rather than in initial telephone calls (see also [13,14]). The majority of quality-of-service studies within patient care are based on surveys, self-reports and/or focus groups [9,15].…”
Section: Introductionmentioning
confidence: 99%
“…Tele-mediated interaction, such as email and telephone counselling, has been examined (Lamerichs and Stommel, 2016;Woods et al, 2015). Studies have centred mainly on professionals' actions and their consequences in interaction, especially counsellors' strategies to give advice while striving to encourage clients' integrity (Butler et al, 2010;Emmison et al, 2011;Poskiparta et al, 2001;Vehviläinen, 2001).…”
mentioning
confidence: 99%
“…Recent developments in conversation analysis suggest that we may be able to identify features of (dis)satisfaction endogenously within conversations (Woods et al, 2015;Sikveland et al, 2016), which is relevant for our second empirical Schegloff, 2007 for in-depth analysis).…”
Section: Introductionmentioning
confidence: 98%